A handbook on legal counselling and interviewing - Ulep, Mauricio C. (Manila Rex Book Store, 1997)
A response to the requests of his students at the University of the East, this book was written by Mauricio Ulep aims to instill to those who would be lawyers the message that proper interviewing and counseling skills can make for cases settled in the law office than in courts, thereby contributing to the speedier administration of service.
Keywords: Interviewing in law practice -- Philippines -- Handbooks, manuals, etc; Attorney and client -- Philippines -- Handbooks, manuals, etc; Practice of law -- Philippines -- Handbooks, manuals, etc